2015
DOI: 10.1093/jee/tov242
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Formate: A Potential Disinfestation Treatment for Eucalyptus Weevil (Gonipterus platensis) (Coleoptera: Curculionidae) in Apples

Abstract: Export of Pink Lady apples from Australia has been significantly affected by infestations of adult eucalyptus weevils (Gonipterus platensis Marelli). These weevils cling tenaciously to the pedicel of apple fruit when selecting overwintering sites. As a result, apples infested with live G. platensis adults lead to rejection for export. Since the Montreal Protocol restricted use of methyl bromide as postharvest treatment, it was necessary to consider alternative safer fumigants for disinfestation of eucalyptus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Studies also showed that the silage fermentation process was improved when formic acid was added to silage . In Australia (AUS), ethyl formate, a derivative of formic acid, is registered for use for the disinfestation of dried fruits, and studies demonstrated that 100 % mortality of adult weevils in apples could be achieved by using ethyl formate, without negatively impacting on the quality or shelf life of the apples . Unlike other pesticides, ethyl formate effectively kills insects, but quickly breaks down to naturally occurring products that are not harmful when ingested in reasonable quantities …”
Section: La Applications and Marketmentioning
confidence: 99%
“…Studies also showed that the silage fermentation process was improved when formic acid was added to silage . In Australia (AUS), ethyl formate, a derivative of formic acid, is registered for use for the disinfestation of dried fruits, and studies demonstrated that 100 % mortality of adult weevils in apples could be achieved by using ethyl formate, without negatively impacting on the quality or shelf life of the apples . Unlike other pesticides, ethyl formate effectively kills insects, but quickly breaks down to naturally occurring products that are not harmful when ingested in reasonable quantities …”
Section: La Applications and Marketmentioning
confidence: 99%
“…The mixture can be applied to apples intended for export in Australia, in order to eradicate the eucalyptus weevil Gonipterus platensis (Agarwal et al . ). An EF application mixed with phosphine gas was also evaluated by Lee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a method has been developed for applying liquid EF with nitrogen gas by using a special vaporizer. The mixture can be applied to apples intended for export in Australia, in order to eradicate the eucalyptus weevil Gonipterus platensis (Agarwal et al 2015). An EF application mixed with phosphine gas was also evaluated by for controlling Aphis gossypii.…”
Section: Introductionmentioning
confidence: 99%
“…Fumigation of the growing equipment used in a mushroom culture can prevent invading purple scum springtails and other species from damaging crops ( and Clift, 2004;Greenslade and Ireson, 1986;Greenslade et al, 2014). Ethyl formate is a naturally occurring compound that has been evaluated as a fumigant for stored grain, fruit, and vegetable applications and has been commercially adopted because of its valuable characteristics of rapid kill and consumer safety (Agarwal et al, 2015;Kim et al, 2013;Ren and Mahon, 2006;Ren et al, 2008). However, EF is highly absorbed in products such as strawberries (Fragaria •ananassa), apples (Malus •domestica), and several types of cut flowers because of their high moisture content and because EF is highly soluble in the water (Agarwal et al, 2015;Lee et al, 2013;Simpson et al, 2004).…”
mentioning
confidence: 99%
“…Ethyl formate is a naturally occurring compound that has been evaluated as a fumigant for stored grain, fruit, and vegetable applications and has been commercially adopted because of its valuable characteristics of rapid kill and consumer safety (Agarwal et al, 2015;Kim et al, 2013;Ren and Mahon, 2006;Ren et al, 2008). However, EF is highly absorbed in products such as strawberries (Fragaria •ananassa), apples (Malus •domestica), and several types of cut flowers because of their high moisture content and because EF is highly soluble in the water (Agarwal et al, 2015;Lee et al, 2013;Simpson et al, 2004). Some studies (Tarr et al, 2007) indicated that EF, as well as EF in combination with 10% carbon dioxide (CO 2 ), could be used for control of sawtoothed grain beetle (Oryzaephilus surinamensis) and confused flour beetle (Tribolium confusum) on dry vine fruit.…”
mentioning
confidence: 99%